Characteristics And Factors Affecting Carbohydrate And Protein Based Food Consumption Patterns - Ayu Sulastri, Merna; Sari, Yulia; Revina Putri , Rani; Lestari, Etika Fuji; Huanza, M (JURNAL AGRIBISAINS, 2025)
Food consumption patterns are fundamental to human well-being, directly influencing health, productivity, and quality of life. This research examines the characteristics, welfare, and factors affecting household consumption patterns in Palembang City. This study uses primary data from an online survey of 72 deliberately selected respondents in Palembang City during November and December 2024. The data was analyzed using descriptive analysis and linear regression methods. The results showed that the people of Palembang City consume carbohydrates and protein as their primary daily food sources. Protein consumption, such as chicken meat and eggs, has met welfare standards. The variables influencing household protein consumption are Household Income (X1), Age (X3), Education (X4), Family Size (X5), and Gender of the Respondent (X6). Meanwhile, the variables affecting household rice consumption (Y2) are Household Income (X1), Family Size (X5), and Gender (X6). The variation in household consumption of protein and rice is significantly influenced by household income. The results of this study can provide information to the government to improve the welfare of the people of Palembang City.